2020
DOI: 10.1002/csc2.20404
|View full text |Cite
|
Sign up to set email alerts
|

Minimum water requirements of Japanese lawngrass for survival during prolonged drought

Abstract: Water restrictions on irrigation are rarely science based and may cause irreversible damage to turfgrass or inadvertently waste water. Our objectives were to evaluate effects of minimum water applications to ‘Meyer’ Japanese lawngrass (Zoysia japonica Steud.) on (a) canopy performance during prolonged drought and (b) survival and recovery thereafter. Meyer was watered weekly with 0–30% reference evapotranspiration (ETo) replacement for ≥56 d in two consecutive summers under a rainout shelter near Manhattan, KS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
1
3
1
Order By: Relevance
“…Deep soils at the research site also likely assisted TF in maintaining PGC during drought periods (Beard, 1973; Bremer, Su, Keeley, & Fry, 2006; Leksungnoen et al., 2012). Another study conducted at the same research site as ours also found zoysiagrass fully recovered from ≥8 wk of drought, even with no water inputs (Hong, Bremer, & Keeley, 2020).…”
Section: Resultssupporting
confidence: 74%
“…Deep soils at the research site also likely assisted TF in maintaining PGC during drought periods (Beard, 1973; Bremer, Su, Keeley, & Fry, 2006; Leksungnoen et al., 2012). Another study conducted at the same research site as ours also found zoysiagrass fully recovered from ≥8 wk of drought, even with no water inputs (Hong, Bremer, & Keeley, 2020).…”
Section: Resultssupporting
confidence: 74%
“…Overall, 'KSUZ 0802' showed good recovery potential in the Kansas experiment. For comparison, a recent study near our site reported 'Meyer' Japanese lawngrass maintained 30% GC after 55 d of drydown and needed 32 d of full irrigation to recover back to 85% GC, although 'Meyer' Japanese lawngrass was mowed at a higher height of cut than 'KSUZ 0802' in this study (Hong and Bremer 2021).…”
Section: Resultscontrasting
confidence: 58%
“…'KSUZ 0802' in nonirrigated plots exhibited acceptable quality until 21 d after treatment in both years. Hong and Bremer (2021) reported nonirrigated 'Meyer' Japanese lawngrass maintained acceptable quality until 28 d with no water in the year 1 and 19 d in the year 2 in a study conducted under a rainout shelter near this site. The differences between years from long-term drought as observed in that study were not apparent in our research, as demonstrated by the similar turf performance metrics at the beginning.…”
Section: Resultsmentioning
confidence: 88%
“…Zoysia japonica (L.) Merr. ‘Meyer’ has been the cold‐tolerant standard since 1951 (Patton & Reicher, 2007) because of its excellent freezing tolerance, but it cannot survive prolonged drought stress without supplemental irrigation (Hong & Bremer, 2021) and is susceptible to large patch disease (caused by Rhizoctonia solani Kühn) and hunting billbugs ( Sphenophorus venatus vestitus Chittenden). Contrastingly, Z. japonica cultivars ‘Empire’ and ‘Palisades’ have excellent drought resistance (Wherley et al., 2014) but inferior freezing tolerance as compared to Meyer (Hinton et al., 2012), limiting their range of adaptation to the warm (southern) climatic regions of the United States.…”
Section: Introductionmentioning
confidence: 99%